Designing towards inward-oriented fashion technology: Demo projects - Toeters, Marina; Toussaint, Lianne; Russell, Kevin; ten Bhömer, Martijn (2020)
Fashion technology designs typically combine sensing technology and actuators to register and respond to information about the environment and/or the human body. The ways in which designers use and integrate these data into garments, however, varies on a scale from highly theatrical and outward-oriented designs to subtle and inward-oriented applications. This pictorial presents five garment designs created between 2013 and 2020, that occupy the more utilitarian and inward-oriented end of the fashion technology spectrum. We demonstrate five designs that combine sensing and actuation, highlighting the benefits of direct biofeedback and of keeping the personal data within the garment. The selection of projects aims to search the right balance between sensing and actuation.